PENGGORENGAN VAKUM UMBI BENGKUANG - -, Suryani (Sistem Informasi, 2010)
Juicy tuber [Pachyrhizuz Erosus L] is the one of holticultural product any location found in Indonesia. It has a typical texture and taste. Usually consumed in a fresh form or used as mixture in the making af canned fruit in food industry. Observing the minimal of the juicy tuber, it is necessary to develop the alternative of the juicy tuber root processing to have a new product with high economical value.This research was conducted to study the influence or effect of the slice thickness and frying time to ward several physical and organoleptical slice thickness and the optimum frying time in the making of the crispy chips of the juicy tuber by using vacuum frying. From this research it is expected to increase the economical value of the juicy tuber and produce the crispy chips product which prosses the physical and organoleptical characteristic accepted by consumer.The result of the physical and organoleptical characteristic test show, the favoristim level of panelist in color chipiness and taste feature of the crispy chips of the juicy tuber produced with the one mm thickness and the frying time averagely three minutes and percentage of moisture in the crispy chips 1,25 â 3,22 on dry weight basis.